Metal-free carbon materials for persulfate-based advanced oxidation process: Microstructure, property and tailoring. (June 2020) - Yu, Jiangfang; Feng, Haopeng; Tang, Lin; Pang, Ya; Zeng, Guangming; Lu, Yue; Dong, Haoran; Wang, Jiajia; Liu, Yani; Feng, Chengyang; Wang, Jingjing; Peng, Bo; et al.
Abstract: Metal-free carbon materials (MFCMs), as newly emerging efficient catalysts in persulfate-based advanced oxidation process (PS-AOP), have exhibited great engineering-application potential for environmental remediation. Nevertheless, the relationships between discrepant catalytic properties and structural/surface characteristics of MFCMs are still ambiguous. Herein, on the basis of the recent advances in experimental and theoretical researches, we provide a systematic review to give insight into the relationships among catalytic activity, microstructure and electrical properties of MFCMs in PS-AOP, where the catalytic diversities of MFCMs in different configurations ( sp 2, sp 3 and amorphous) and dimensionalities (zero to three dimensional) are discussed in detail. Besides, the effects of different tailoring engineering approaches, such as structure defect, heteroatom doping, and regulation of pore structure and surface functional groups, on the catalytic activity of MFCMs in PS-AOP are thoroughly summarized. Finally, critical discussion and future prospects in the aspects of mechanism exploration and possible materials development are proposed to confront the existing challenges in the application of MFCMs in PS-AOP.